2019
DOI: 10.1002/leg3.20
|View full text |Cite
|
Sign up to set email alerts
|

Effect of germination and roasting on the proximate composition, total phenolics, and functional properties of black chickpea (Cicer arietinum)

Abstract: Germinated and microwave roasted black chickpea were evaluated for physical, proximate, pasting, functional, and antioxidant properties. A significant variation was observed in quality of grain upon germination and roasting. The effect of germination and roasting on functional groups was analyzed using Fourier‐transform infrared spectroscopy. The results showed that germination improved the physical and pasting properties, whereas roasting enhanced the functional properties. The lightness of germinated grains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 29 publications
11
25
0
Order By: Relevance
“…Kaur et al, (2005) reported protein content of 16.1-21.3% for five Desi and one Kabuli chickpea cultivars. The reduce in protein content of roasting was found to be in accordance with the results reported by Kumar et al, (2020) for the roasting of black chickpea. The content of crude fiber for different treatments varied from 4.68-4.72%.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Kaur et al, (2005) reported protein content of 16.1-21.3% for five Desi and one Kabuli chickpea cultivars. The reduce in protein content of roasting was found to be in accordance with the results reported by Kumar et al, (2020) for the roasting of black chickpea. The content of crude fiber for different treatments varied from 4.68-4.72%.…”
Section: Resultssupporting
confidence: 90%
“…Although methods of processing chickpea cause loss protein in it, but the protein quality is preserved by roasting to a higher content than by dry heat treatment. In the other hand, roasting is a high temperature controlled time process known to improve the digestibility, shelf life, and antioxidant properties (Kumar et al, 2020). Exposure at high temperature leads upon roasting to development of characteristic flavor, taste, some nutritional quality and crispy texture in grains that allure the consumers (Jogihalli et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Ragaee et al (2014) noticed both effects-an increase or decrease of phenolics-after roasting, which is the process closest to baking. Additionally, phenolics from germinated or microwaveroasted black chickpea, as well as solid-state fermented lentils, showed a significant increase after these processing methods were applied (Dhull, Punia, Kidwai, et al, 2020;Kumar et al, 2020). Our results showed an increase of phenolics after baking for the samples containing a low amount of phenolics in the raw samples (RL, GSP, YSP, CC, and NB), whereas a decrease was observed in those with a high phenolic content in the raw samples (GL, RKB, BB, and PB).…”
Section: Polyphenolsmentioning
confidence: 99%
“…Differences between the dough samples are not easy to detect from the raw spectra, since all of them exhibit the same IR bands related to the presence of lipid and chitin (2900 and 2850 cm −1 ), lipid (around 1700-1740 cm −1 ), protein (1650 and 1500 cm −1 ), and carbohydrates and chitin (from 1200 to 900 cm −1 ), with a similar absorbance. Comparing the spectral information from the ingredients used in the dough and snack formulation (Figure 2), it can be observed that chickpea, curry, A. diaperinus, and L. migratoria powder showed a broad IR band from 3000 to 3500 cm −1 , which originated from the stretching of O-H bonds most likely coming from carbohydrates, fiber, and water [24]. Moreover, all these spectra exhibited two narrower IR bands at around 2900 and 2850 cm −1 , characteristics of asymmetrical and symmetrical stretching vibrations from C-H bonds from methyl groups presumably caused by lipids or, in the case of insect powders, lipids and chitin.…”
Section: Spectral Information Of Ingredients and Doughsmentioning
confidence: 99%